Electromyographic evidence of reduced emotion mimicry in individuals with a history of non-suicidal self-injury - Ziebell, Laura (PLoS One, 2020)
Engaging in facial emotion mimicry during social interactions encourages empathy and functions as a catalyst for interpersonal bonding. Decreased reflexive mirroring of facial expressions has been observed in individuals with different non-psychotic disorders, relative to healthy controls. Given reports of interpersonal relationship difficulties experienced by those who engage in non-suicidal self-injury (NSSI), it is of interest to explore facial emotion mimicry in individuals with a history of this behaviour (HNSSI). Among other things, this will enable us to better understand their emotion regulation and social interaction challenges. Surface facial electromyography (fEMG) was used to record the reflexive facial mimicry of 30 HNSSI and 30 controls while they passively observed a series of dynamic facial stimuli showing various facial expressions of emotion. Beginning with a neutral expression, the stimuli quickly morphed to one of 6 prototypic emotional expressions (anger, fear, surprise, disgust, happiness, or sadness). Mimicry was assessed by affixing surface electrodes to facial muscles known to exhibit a high degree of electrical activity in response to positive and negative emotions: the corrugator supercilii and the zygomaticus major. HNSSI participants, relative to controls, exhibited significantly less electrical activity in the corrugator muscle in response to viewing angry stimuli, and significantly less of an expected relaxation in muscle activity in response to viewing happy stimuli. Mirroring these results, greater endorsement of social influence as a motivator for engaging in NSSI was associated with less mimicry, and greater endorsement of emotion regulation as a motivator was associated with greater incongruent muscle response when viewing happy faces. These findings lend support to the theory that social interaction difficulties in HNSSI might be related to implicit violations of expected social rules exhibited through facial mimicry nonconformity.